1999
DOI: 10.1093/oxfordjournals.molbev.a026204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of the parasitic protozoan Giardia intestinalis

Abstract: The long-standing controversy regarding whether Giardia intestinalis is a single species prevalent in both human and animal hosts or a species complex consisting of morphologically similar organisms that differ in host range and other biotypic characteristics is an issue with important medical, veterinary, and environmental management implications. In the past decade, highly distinct genotypes (some apparently confined to particular host groups) have been identified by genetic analysis of samples isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(174 citation statements)
references
References 40 publications
10
155
0
9
Order By: Relevance
“…In addition, an 18S rDNA and gdh-specific DNA sequence analysis was performed. Clearly two genotype groups could be recognised, similar to the two assemblages A and B described by Homan et al (1998) and Monis et al (1999) ( Table 3). In total, 34 samples were identified as Giardia Assemblage A, 64 as Assemblage B and two samples remained negative.…”
Section: Genotyping Of Human Giardia Isolatessupporting
confidence: 54%
See 3 more Smart Citations
“…In addition, an 18S rDNA and gdh-specific DNA sequence analysis was performed. Clearly two genotype groups could be recognised, similar to the two assemblages A and B described by Homan et al (1998) and Monis et al (1999) ( Table 3). In total, 34 samples were identified as Giardia Assemblage A, 64 as Assemblage B and two samples remained negative.…”
Section: Genotyping Of Human Giardia Isolatessupporting
confidence: 54%
“…The Dutch goat and sheep samples clustered together with the calf isolate (AY178740), Assemblage E and far distant from the Dutch dog samples (AY827498 and AY827499), which clustered together with the Australian dog (U60986), Assemblage D. The Dutch roe deer gdh sequence clustered together with the human isolates of Assemblage A, however, not in the same subcluster as the human Assemblage A isolates analysed. In addition, some animal gdh DNA sequences derived from GenBank clustered together with human Assemblage B. Subgenotyping of our human Assemblage B-derived gdh sequences showed that those with GenBank accession number AY826193 were located in the cluster of Australian human isolates of Assemblage B group III (AY178756/AF069059) (Monis et al, 1999), those with accession number AY826191 clustered in Assemblage B group IV containing the Australian human isolates (AY178738/AY178739, AY178754, L40508), the Canadian and Czech dog isolates (AY178750/AY178749) and the Czech chinchilla isolates (AY178751). Our human isolates with accession numbers AY826192, AY826197 belonging to Assemblage B clustered together in the IV-like group together with the marmosets AY178752, AY178753.…”
Section: Phylogenetic Analysis Of 18s Rrna and Gdh Dna Sequencesmentioning
confidence: 91%
See 2 more Smart Citations
“…1995; Monis et al. 1999). A very low frequency of recombination between assemblages led to the suggestion of their genetic isolation and mutual speciation (Xu et al.…”
Section: Discussionmentioning
confidence: 99%